Infantile-Onset Pompe Disease - ASHRAFI, Mahmoud Reza; TAVASOLI, Alireza (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Ashrafi MR, Tavasoli AR. Infantile-Onset Pompe Disease. Iran J Child Neurol Autumn 2012; 6:4(suppl. 1):7-9. Pls see PDF. References: 1. Kishnani PS, Steiner RD. Pompe disease diagnosis and management guidelines. American J med genetic. 2006 .Vol; 8; no5. 2. Case SE, Beckemyer AA. Infantile pompe disease on ERT-Updateonclinicalpresentation,musculoskeletal management, and Exercise considerations. American J med genetic.160C:69-79(2012). 3. Rocco MD,Buzzi D. Glycogen storage disease type II:clinical overview. Acta myologica. 2007; XXVI; P.42-44. 4. Fenichel GM.Clinical pediatric neurology. Sixth edition.2009; p.174,188. 5.Swaiman KF, Ashwal S. Swaimans’ pediatric neurology. Fifth edition .2012 .Vol.1,p.378-380.